2013
DOI: 10.3748/wjg.v19.i3.394
|View full text |Cite
|
Sign up to set email alerts
|

Single-incisionvsthree-port laparoscopic cholecystectomy: Prospective randomized study

Abstract: SILC is a safe and feasible approach in selected patients. The main advantages are a better cosmetic result and less pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…IAP of all the patients in the present study was maintained at 12 mmHg. Ming-Xin Pan et al [38] , Maria F, et al [7] and many others also used IAP of either 12 mmHg or 13 mm Hg Conversion rate of present study is 1.36%. From time to time, various authors have reported various conversion rate viz.…”
Section: Discussionsupporting
confidence: 49%
“…IAP of all the patients in the present study was maintained at 12 mmHg. Ming-Xin Pan et al [38] , Maria F, et al [7] and many others also used IAP of either 12 mmHg or 13 mm Hg Conversion rate of present study is 1.36%. From time to time, various authors have reported various conversion rate viz.…”
Section: Discussionsupporting
confidence: 49%
“…Conversion was required in 6 patients of a single study, specifically 4 patients subjected to singleincision surgery with curved instruments and 2 conventional laparoscopic cholecystectomies [33]. Bile leak or subhepatic collection was reported in 5 studies [19,23,27,30,34], with an equal distribution among treatment arms (3 patients in each treatment group and 4 patients in the control group). The diagnosis was made through a drain tube in two studies which provided relevant information [27,34].…”
Section: Outcomes Of Individual Studiesmentioning
confidence: 99%
“…It has been argued against single port laparoscopy that there could be a higher rate of incisional hernia. [26][27][28][29][30][31] We did not find any such difference, and we actually believe that it is easier to close the fascial wound after single port laparoscopy because the larger skin incision facilitates the closing. Longer follow-up time should in any case be employed to re-evaluate whether incisional hernia rates continue to be equal in both groups.…”
Section: Discussionmentioning
confidence: 75%